The Need for Sustainable Teleconsultation Systems in the Aftermath of the First COVID-19 Wave - Giunti, Guido; Goossens, Richard; De Bont, Antoinette; Visser, Jacob J; Mulder, Mark; Schuit, Stephanie C E (JMIR Publications, 2020)
The physical and social distancing measures that have been adopted worldwide because of COVID-19 will probably remain in place for a long time, especially for senior adults, people with chronic conditions, and other at-risk populations. Teleconsultations can be useful in ensuring that patients continue to receive clinical care while reducing physical crowding and avoiding unnecessary exposure of health care staff. Implementation processes that typically take months of planning, budgeting, pilot testing, and education were compressed into days. However, in the urgency to deal with the present crisis, we may be forgetting that the introduction of digital health is not exclusively a technological issue, but part of a complex organizational change problem. This viewpoint offers insight regarding issues that rapidly adopted teleconsultation systems may face in a post-COVID-19 world.